(untitled) (Damascus University Journal of agriculture sciences, 2026)
The research was carried out during the 2021 agricultural season at the Qarhata Research Station of the General Commission for Scientific Agricultural Research, with the aim of studying the response of 13 genotypes of sesame to water stress conditions applied during the flowering stage. The experiment was carried out according to a randomized complete block design (RCBD), in split-plot arrangement, in three replications. The results showed significant differences (P≤0.05) in the relative water content in the leaves, the average percentage of solutes leaking through the cytoplasmic membranes, and the protein percentage between the treatments, the genotypes, and the interaction between them. As for oil, the results showed that there were no significant differences between the genotypes and the interaction. between treatments and genotypes, while significant differences (P≤0.05) were observed between treatments. The response of the genotypes to the applied stress varied, as the average relative water content in the leaves was significantly higher for the genotypes Hourani 3, Hourani 1, and Hourani 11, and the average percentage of solutes leakage was significantly higher for the control genotypes Hourani and Hourani 5, and the average protein percentage in the seeds was significantly higher for the two genotypes. Hourani 6 and Hourani 5 genotypes, and no significant differences were observed in the percentage of oil in the seeds. The Zuri3 genotype achieved the lowest rates of decrease in the average relative water content, while the Hourani6 genotype achieved the highest rates of increase in the average percentage of leaked solutes, and the highest rates of increase in the oil percentage in seeds, and the two genotypes, Zuri1 and Hourani11, had the highest rates of increase in the protein percentage in seeds.